Bacteraemia due to OXA‐48‐carbapenemase‐producing Enterobacteriaceae: a major clinical challenge. (12th December 2012) - Navarro‐San Francisco, C.; Mora‐Rillo, M.; Romero‐Gómez, M. P.; Moreno‐Ramos, F.; Rico‐Nieto, A.; Ruiz‐Carrascoso, G.; Gómez‐Gil, R.; Arribas‐López, J. R.; Mingorance, J.; Paño‐Pardo, J. R.; Allerberger, F.
Abstract Bacteraemia due to carbapenemase‐producing Enterobacteriaceae is an emerging medical problem. Management of this entity is complicated by the difficulty in identifying resistance patterns and the limited therapeutic options. A cohort study was performed including all episodes of bloodstream infection due to OXA‐48‐producing Enterobacteriaceae (O48PE), occurring between July 2010 and April 2012. Data on predisposing factors, clinical presentation, therapy and outcome were collected from medical records. There were 40 cases of bacteraemia caused by O48PE, 35 Klebsiella pneumoniae and five Escherichia coli. Patients were elderly with significant comorbidities (57.5% underlying malignancy). Thirty‐five cases (87.5%) were nosocomial, and five (12.5%) were healthcare‐associated. Patients had frequently been exposed to antibiotics and to invasive procedures during hospitalization. The most common source of bacteraemia was the urinary tract followed by deep intra‐abdominal surgical site infection. Clinical presentation was severe sepsis or shock in 18 cases (45%). Extended‐spectrum β‐lactamase production was detected in 92.5% of isolates. MIC90 for ertapenem, imipenem and meropenem were 32, 16 and 16 mg/L, respectively. Most frequently preserved antibiotics were amikacin, colistin, tigecycline and fosfomycin. These antibiotics combined are the basis of targeted therapies, including carbapenem in selected cases. Median delay in starting clinically adequate and microbiologically appropriate treatment was 3 days. Crude mortality during admission and within 30 days from bacteraemia was 65% and 50%, respectively. Bloodstream infections caused by O48PE have a poor prognosis. Delay in diagnosis and in initiation of optimal antimicrobial therapy is frequent. Suspicion and rapid identification could contribute to improving outcomes.